(untitled) (Economics and region, 2022)
The article substantiates the need to introduce innovations into the activities of tourism enterprises as a tool for increasing competitiveness in the market of tourism services. The COVID-19 pandemic and the full-scale invasion of Russia had an extremely negative impact on the development of the tourism business in Ukraine, and therefore tourism enterprises were faced with the task of how to maintain their position in the service market. As a result of the study, a methodological approach to the assessment of the innovative capacity of the Ukrainian tourism industry was developed using the integral method and SPACE analysis, which allows to assess the potential in relation to the main areas of strategic management, the development of which ensures the efficiency of the enterprise: attractiveness, competitiveness, financial strength and stability. The use of SPACE analysis also makes it possible to determine the company’s development strategies, the main factors that ensure the effectiveness of the strategy. The need for a high-quality and reliable assessment of the level of innovation in the formation of the company’s development strategy is substantiated, which makes it possible to make a decision on the implementation of measures to achieve the company’s goals or to search for opportunities and reserves to increase the level of production potential.